2015
DOI: 10.1530/eje-15-0200
|View full text |Cite
|
Sign up to set email alerts
|

Multiple aberrant hormone receptors in Cushing's syndrome

Abstract: The mechanisms regulating cortisol production when ACTH of pituitary origin is suppressed in primary adrenal causes of Cushing's syndrome (CS) include diverse genetic and molecular mechanisms. These can lead either to constitutive activation of the cAMP system and steroidogenesis or to its regulation exerted by the aberrant adrenal expression of several hormone

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 157 publications
1
49
1
2
Order By: Relevance
“…Peritumoral adrenal tissue from patient #1 did not express GIPR. Interestingly, as reported previously (11), concomitant aberrant expression of one or more G protein-coupled hormone receptors was detected in one adenoma (from patient #4) and in 3 hyperplasia samples (from patient #6, #10, and #11) in addition to GIPR (Supplemental Figure 2).…”
Section: Resultssupporting
confidence: 80%
“…Peritumoral adrenal tissue from patient #1 did not express GIPR. Interestingly, as reported previously (11), concomitant aberrant expression of one or more G protein-coupled hormone receptors was detected in one adenoma (from patient #4) and in 3 hyperplasia samples (from patient #6, #10, and #11) in addition to GIPR (Supplemental Figure 2).…”
Section: Resultssupporting
confidence: 80%
“…A transcriptome study identified increased mRNA of additional GPCRs; motilin, gamma-amino-butyric acid (GABBR1) and a-2 adrenergic (ADRA2A) receptors (Assie et al 2010). Responses to up to four stimuli has been reported in 50% of the patients indicating that multiple aberrant receptors may co-exist in each patient (Hofland et al 2013, El Ghorayeb et al 2015, St-Jean et al 2018. The molecular mechanisms leading to ectopic GPCRs expression in adrenal tissue are not known.…”
Section: Pathophysiologymentioning
confidence: 99%
“…In particular, 5-HT, produced by mast cells located in zona glomerulosa, is able to stimulate production of corticosteroids through a paracrine mechanism involving the 5-HT receptor type 4 (5-HT 4 ) expressed by adrenocortical cells (Contesse et al, 2002; Lefebvre et al, 2001, 1993, 1992). Moreover, overexpression of 5-HT 4 receptors has been reported in adrenal tumors responsible for hyperaldosteronism and hypercortisolism (Cushing’s syndrome) (Bertherat et al, 2005; Cartier et al, 2005; El Ghorayeb et al, 2015; Lefebvre et al, 2002). Deciphering the mechanism of action of 5-HT 4 receptors in adrenal is critical to understand the role of the serotonergic control of corticosteroid secretion in physiological and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%